Re-making the middle: Dis-intermediation in international context. (May 2014) - Lubienski, Christopher
Recent reforms in England's education system have been justified on the grounds that other countries have pursued similar approaches to education reform. Many such policies that by-pass or otherwise diminish meso-level institutions demonstrate a commitment to the idea of devolving authority to local actors. The current reforms in England and elsewhere reconfigure governance structures to diminish intermediate-level institutions on the grounds that these reforms lead to more effective and equitable educational systems. But in lieu of compelling evidence of such an impact, it appears that such policies are often instead simply a political attack on meso-level authorities, and may in fact represent an opportunity for new policy players to occupy the space left by receding meso-level institutions. This article surveys some of the specific policies that have emerged from recent policy trends, particularly those that have undercut established intermediate-level institutions in the USA and New Zealand. Reviewing the empirical record from these cases, I argue that, rather than simply devolving power away from intermediate authorities to local actors in order to produce more effective or equitable outcomes, many of these reforms have been more successful instead in creating the conditions in which new, non-state actors are able to accrue policy power for themselves.